2005
DOI: 10.1136/ard.2004.032151
|View full text |Cite
|
Sign up to set email alerts
|

Increased C reactive protein in response to acute stress in patients with rheumatoid arthritis

Abstract: The increase in the inflammatory marker CRP, which was specific to patients with RA, combined with the haemostatic, rheological, and haemodynamic reactions to the stress task, over and above the already high baseline levels, could underlie the increased risk for myocardial infarction in this vulnerable patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 34 publications
6
61
1
Order By: Relevance
“…Thus, the experimental manipulations induced increase in IL-6 values which were similar to those at risk for MI. Furthermore, the mental stress task used in the present study elicited a physiological response similar to previous studies (Paine et al, 2013a;Veldhuijzen van Zanten et al, 2005. Heart rate, blood pressure and total numbers of white blood cells increased in all conditions during the mental stress task (figure 2).…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Thus, the experimental manipulations induced increase in IL-6 values which were similar to those at risk for MI. Furthermore, the mental stress task used in the present study elicited a physiological response similar to previous studies (Paine et al, 2013a;Veldhuijzen van Zanten et al, 2005. Heart rate, blood pressure and total numbers of white blood cells increased in all conditions during the mental stress task (figure 2).…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies have suggested a role for baseline inflammation on physiological responses to mental stress (Roupe van der Voort et al, 2000;Shah et al, 2006;Veldhuijzen van Zanten et al, 2005). In the current study, we used two established experimental paradigms to induce inflammation in healthy participants to specifically assess the influence of inflammation on the oxidative stress responses to mental stress.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Recently, the impact of stress and hormones on the regulation of CRP production has been discussed [19,20].…”
mentioning
confidence: 99%